AB0293 Can we safely start biological therapy in rheumatic patients with prior history of active tuberculosis?. (23rd January 2014) - Romão, V. C.; Saavedra, M. J.; Vieira-Sousa, E.; Costa, M.; Polido-Pereira, J.; Rodrigues, A. M.; Ramos, F.; Macieira, C.; Capela, S.; Resende, C.; Madruga Dias, J.; Ponte, C.; et al.
Abstract : Background: The risk of tuberculosis (TB) reactivation in rheumatic patients who had previously treated active TB is currently unclear. In addition, current screening procedures and decision for latent TB (LTB) treatment in these patients have not been addressed in guidelines for TB prevention. Objectives: The aim of this study was to analyze patients from a single center with prior history of active TB who started biological therapies. Methods: We included patients treated with biological therapy and registered in Reuma.pt that had a diagnosis of active TB preceding treatment start. Results: Eight patients with previous active TB were identified, 4 with rheumatoid arthritis (RA), 3 with spondyloarthritis (SpA) and 1 with psoriatic arthritis (PsA). Pulmonary TB was the diagnosis in all cases. Active TB occurred on average 40 ± 11 (minimum 17, maximum 50) years before the start of biological therapy. Five patients were treated for active TB during 12 (SpA1, SpA2 ), 18 (RA1, RA4 ) and 24 months (RA3 ). For the remaining 3 patients we could not obtain accurate data on the duration of TB treatment. Prior to the start of biological therapy, 6 patients were treated for LTB with isoniazid for 6 to 12 months because of positive screening: prior TB history, radiographic changes and, in all but one case (RA1 ), positive tuberculin skin test (TST). Two patients were not treated for LTB, one (RA2 ) because biological treatment was started in 2001, prior to the introduction of screening guidelines, and the other (RA3 ) because the pulmonologist considered that previous treatment at the time of TB diagnosis with quadruple anti-tubercular therapy for 2 years plus the current negative screening tests (TST, chest X-ray) excluded the need for additional therapy. Three SpA patients were treated with etanercept and one PsA patient with infliximab; RA patients were started on different biologicals: golimumab, infliximab, tocilizumab and etanercept, respectively. At the time of starting therapy, all patients had highly active disease, as measured by DAS28 or ASDAS-ESR. All but two patients (SpA1, SpA3 ) eventually stopped biological treatment and in two cases therapy was switched (SpA2, infliximab and adalimumab; RA1, abatacept). One patient (PsA) developed pulmonary TB 18 months after the start of infliximab, following contact with a documented TB case. Conclusions: In our center, patients with previously treated active TB were screened and treated for LTB. None of the patients developed TB reactivation. The only reported case was considered a new infection. Disclosure of Interest: None Declared